The reading of scientific articles. Interview to undergraduate students - Castro-Rodríguez, Yuri (2020)
Scientific articles reading is part of a researcher habit. Meanwhile, for students it is a teaching-learning strategy to familiarize themselves with the widespread scientific knowledge, writing styles, clinical case management and methods comprehension. In the present interview the opinion of South American students from three dental faculties (Universidad Nacional de San Marcos-Perú, Universidad de San Sebastián-Chile and Universidad Nacional de Córdoba-Argentina) are compiled regarding the reading and usefulness of scientific journals. The information collected allows us to explore the student perceptions about scientific articles reading.